The authority of the Court and the peril of politics - Breyer, Stephen G., 1938- (Harvard University Press, 2021)
"Americans increasingly believe the Supreme Court is a political body in disguise. But Justice Stephen Breyer disagrees. Arguing that judges are committed to their oath to do impartial justice, Breyer aims to restore trust in the Court. In the absence of that trust, he warns, the Court will lose its authority, imperiling our constitutional system"--